Iran Hostage Crisis: A Sphere Full of Distrust and Failure - Siti Adela (Jurnal Sentris, 2017)
There is no doubt that Iran hostage crisis has left quite a profound scar in U.S. history. It also signaled the inability of U.S. government, through President Jimmy Carter, to solve the problem that U.S. faced in the past. This paper delves into the brief history of the diplomatic crisis that happened between U.S. and Iran, also it stressed on how Carter tried to engage Iran in several warm negotiations, including the so-called ‘failed’ mission, which were mostly greeted by refusal from Iran itself